Pengaruh Harga Jual dan Biaya Operasional terhadap Pendapatan Nelayan Kampung Menawi Distrik Angkaisera Kabupaten Kepulauan Yapen - Agoeng Karyanto; Dedy Hidayat; Korinus Reri (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2026)
This study aims to determine the effect of selling price and operational costs on fishermen’s income in Menawi Village, Angkaisera District, Kepulauan Yapen Regency. The population in this study consisted of all fishermen in Menawi Village, Angkaisera District, Kepulauan Yapen Regency. The research sample included 15 fishermen. The data collection technique used in this study was observation through interviews with fishermen, and the data were analyzed using multiple linear regression analysis with the assistance of SPSS 21.0 for Windows. The results of this study indicate that (a) there is a significant simultaneous effect of selling price and operational costs on fishermen’s income in Menawi Village, Angkaisera District, Kepulauan Yapen Regency; (b) there is a positive and significant partial effect of selling price and operational costs on fishermen’s income in Menawi Village, Angkaisera District, Kepulauan Yapen Regency, which can form the basis for economic policy and natural resource management in the fisheries sector. This research is expected to provide insight for policymakers in formulating strategies to increase fishermen's incomes through improved selling prices and more efficient operational cost management.